A CLINICO-PATHOLOGICAL STUDY OF WILSONS DISEASE; 8 YEARS’ EXPERIENCE OF A TERTIARY CARE HOSPITAL - Ali, Naurin; Aaraj, Sahira; Farooqui, Fareeha; Malik, Munir Iqbal (Journal of Ayub Medical College Abbottabad, 2021)
Background: Wilson’s disease is a genetically transmitted disease and has a variety of clinical manifestations. We evaluated the various clinical and biochemical presentations of Wilson’s disease (WD) at different ages. Methods: This cross-sectional study was conducted in Shifa international hospital and Shifa Foundation Falahi Clinic (SFFC), Islamabad. Data from Jan 2010 to Dec 2018 was retrieved from hospital medical record on a structured proforma. All patients who had twenty-four hours urinary copper level of ‰¥100 mcg/day were included in the study. Their presenting symptoms, clinical signs and lab investigations were noted. Results: Mean age was 13±4.588 years. Male to female ratio was 1.5:1. Hepatic disease was seen in 35 (68.6%) patients mainly in <10 yrs age group. Pure neurological Wilson’s was seen in 14 (27.45%) cases, which were >10 years of age while 18(35.3%) had hepato-neurological manifestations. Keyser Fleischer rings were present in 26 (51%) of total patients and 14 (100%) of neurological cases. Hepatic transaminases were elevated in 36 (70 %) patients. Low serum cerruloplasmin was seen in 37 (72.5%) cases. Mean value of haemoglobin was 10.38±2.772. Mean 24 hours urinary copper was 597.6±605.446. Consanguinity was seen among 33 (64.7%) families. Family history of WD was positive in 21 (41.2%) patients. Conclusion: Hepatic form of WD is more common, yet neurological presentation is seen in patients >10 years of age. Keywords: Hepatolenticular degeneration; Keysher Fleischer rings; Neurological; Wilson’s disease (WD); Copper metabolism